Genetic Variation in Heat Tolerance of the Coral Platygyra Daedalea Indicates Potential for Adaptation to Ocean Warming - Elder, Holland; Weis, Virginia M.; Montalvo-Proano, Jose; Mocellin, Veronique J. L.; Baird, Andrew H.; Meyer, Eli; Bay, Line K. (Frontiers in Marine Science, 2022)
Ocean warming represents the greatest threat to the persistence of reef ecosystems. Most coral populations are projected to experience temperatures above their current bleaching thresholds annually by 2050. Adaptation to higher temperatures is necessary if corals are to persist in a warming future. While many aspects of heat stress have been well studied, few data are available for predicting the capacity for adaptive cross-generational responses in corals. Consistent sets of heat tolerant genomic markers that reliably predict thermal tolerance have yet to be identified. To address this knowledge gap, we quantified the heritability and genetic variation associated with heat tolerance in Platygyra daedalea from the Great Barrier Reef. We tracked the survival of ten quantitative genetic crosses of larvae produced form six parental colonies in a heat tolerance selection experiment. We also identified allelic shifts in heat-selected (35°C) survivors compared with paired, non-selected controls (27°C). The narrow-sense heritability of survival under heat stress was 0.66 and a total of 1,069 single nucleotide polymorphisms (SNPs) were associated with different survival probabilities. While 148 SNPs were shared between several experimental crosses, no common SNPs were identified for all crosses, which suggests that specific combinations of many markers are responsible for heat tolerance. However, we found two regions that overlap with previously identified loci associated with heat tolerance in Persian Gulf populations of P. daedalea, which reinforces the importance of these markers for heat tolerance. These results illustrate the importance of high heritability and the complexity of the genomic architecture underpinning host heat tolerance. These findings suggest that this P. daedalea population has the genetic prerequisites for adaptation to increasing temperatures. This study also provides knowledge for the development of high throughput genomic tools which may screen for variation within and across populations to enhance adaptation through assisted gene flow and assisted migration.